2017
DOI: 10.1158/1078-0432.ccr-16-0742
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Feedback Loop of lncRNA-PVT1 and FOXM1 Facilitates Gastric Cancer Growth and Invasion

Abstract: The long, noncoding RNA (lncRNA) is an important epigenetic regulator with a critical role in human tumors. Here, we aimed to investigate the clinical application and the potential molecular mechanisms of in gastric cancer tumorigenesis and progression. The expression level of was determined by RT-qPCR analysis in 190 pairs of gastric cancer tissues and adjacent normal gastric mucosa tissues (ANT). The biologic functions of were assessed by and functional experiments. RNA protein pull-down assays and LS/MS mas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
207
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(216 citation statements)
references
References 28 publications
7
207
1
Order By: Relevance
“…A total of 2585 participants were included with a maximum sample size of 593 and a minimum sample size of 30. Among the 15 articles, the digestive system malignancies assessed in these studies included esophageal carcinoma (2 articles) [39, 44], gastric cancer (6 articles) [22, 33, 38, 40-42], colorectal cancer (2 articles) [20, 37], hepatocellular carcinoma (2 articles) [21, 34], pancreatic cancer (3 articles) [35, 36, 43]. Among the eligible articles, one came from Japan [20], one came from Portugal [36] and the rest of 13 articles were came from China [21-22, 33-35, 37-44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2585 participants were included with a maximum sample size of 593 and a minimum sample size of 30. Among the 15 articles, the digestive system malignancies assessed in these studies included esophageal carcinoma (2 articles) [39, 44], gastric cancer (6 articles) [22, 33, 38, 40-42], colorectal cancer (2 articles) [20, 37], hepatocellular carcinoma (2 articles) [21, 34], pancreatic cancer (3 articles) [35, 36, 43]. Among the eligible articles, one came from Japan [20], one came from Portugal [36] and the rest of 13 articles were came from China [21-22, 33-35, 37-44].…”
Section: Resultsmentioning
confidence: 99%
“…Another research further explored the biological role of lncRNA PVT1 in GC, and confirmed that lncRNA PVT1 could accelerate cell proliferation through epigenetically regulating p15 and p16 [33]. PVT1 enhanced cancer cell proliferation and invasion in vitro and in vivo , through the positive feedback loop of PVT1-FOXM1, suggesting that PVT1 could be a potential therapeutic target for gastric cancer [40]. …”
Section: Discussionmentioning
confidence: 99%
“…However, rectum adenocarcinoma (READ), skin cutaneous melanoma (SKCM), and stomach adenocarcinoma (SKAD) in the TCGA dataset were correlated with a good prognosis although the results were not statistically significant; their corresponding HR values were 0.786 (95%CI: 0.379-1.629, P= 0.517) ‚ 0.92 (95%CI: 0.742-1.141, P= 0.449) and 0.912 (95%CI: 0.702-1.183, P= 0.486) , respectively. We reviewed the relevant studies and found that the high PVT1 level was associated with worse outcomes in gastric cancer and colorectal cancer [22, 26, 30, 33, 36] and that there was no corresponding report for melanoma. The inconsistent results in the TCGA and literature studies in these tumors may be caused by sampling error and publication bias.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR plays an important role in cell migration, proliferation, cell cycle regulation and other physiological processes [7]. EGFR is up-regulated in various cancers including gastric cancer [12,13], and is recognized as oncogenic driver in tumorigenesis. LncRNA EGFR antisense RNA 1 (EGFR-AS1) is a 2.8-kb transcript that transcribes in the antisense strand of EGFR [17,18].…”
Section: Introductionmentioning
confidence: 99%